Elevated NLR and PCT levels and reduced GCS score predict 90-day mortality in heatstroke: findings from a 13-year retrospective cohort study - Guo, Huili; Ji, Jingjing; Ouyang, Leifang; Wang, Conglin; Jia, Jinxin; Liu, Zhifeng (Frontiers in Medicine, 2025)
Background and objectiveHeatstroke is the most severe heat-related illness and is associated with high mortality rate. Inflammation and immune dysfunction are considered the key pathophysiological processes of heatstroke. The neutrophil-to-lymphocyte ratio (NLR) can reflect the states of innate and adaptive immune systems. The aim of the present study was to explore the predictive role of the NLR in heatstroke patients.MethodsThis single-center retrospective cohort study included all patients with exertional-heatstroke (EHS) admitted to the intensive-care-unit (ICU) of the General Hospital of Southern Theater Command of PLA from June 2009 to May 2022. The dynamic changes in the main immune cell counts and ratios were recorded.ResultsA total of 232 patients were enrolled. Survivors had decreased NLRs 24 h after admission, while nonsurvivors had continuously increased NLRs after admission. The AUC for the 24-h NLR was 0.928, with a cutoff of 11.981. The patients were divided into NLR-high (NLR > 11) and NLR-low (NLR ≤ 11) groups based on their 24-h NLRs. Patients in the NLR-high group had increased 90-day mortality. According to the multivariate analysis, an increased PCT level and decreased GCS score were independent risk factors for death in heatstroke patients with an NLR over 11, with odds ratios of 1.0999 (95% CI: 1.0050–1.2038, p value: 0.03863) and 0.6836 (95% CI: 0.5246–0.8908, p value: 0.00486), respectively.ConclusionAn NLR greater than 11 in the early phase could be an independent predictor of prognosis in heatstroke patients, and an increased PCT level and decreased GCS score were risk factors for a poor prognosis.